Aspectos do cotidiano e práticas culturais : um recorte em Machado de Assis e em Lima Barreto - José Wellington Dias Soares (2015)
Our work has as its main objective an analysis about the historicity of Brazilian/carioca quotidian taking the years from 1880 to 1920. Considering literature as a kind of special source that registers different aspects of the quotidian as important cultural elements required for understanding the idea of how Brazilian character is formed, we take the novels written by Machado de Assis (1839 – 1908) and Lima Barreto (1881 – 1922) as the corpora of our research. The literary works chosen do not consist on an aleatory choice. They are different on what concerns to the literary purposes they show, being responsible for shining a light on a vast and complex material about private and public lives, including the ways how part of the carioca population act and think. The way both novelists make cultural, social and everyday relations appear in their fictional works allows a dialogue with their own journalistic writings, providing the searcher information about Brazilian reality. Intending to set up a connection between fiction and reality we compare their novels to their chronicles. Therefore, it is possible to examine how both instances come closer once aspects that are common to chronicles can be observed in the novels. The same way, those characteristics related to novels can also be identified in their chronicles. Thus, our sources about the quotidian historicity had to be amplified once the main function of a chronicle is the everyday reality, though it is not free of keeping fictional elements. On the other hand, while developing the analysis of the quotidian in the context of historical dynamism, we will discuss the peculiarity of the literary registry of historical events, aiming to understand the relations between history and fiction. Space and time are, for their turn, essential elements for our work because they assume significant meanings in everyday habits and activities. Over and above that, the idea of space and time has a particular meaning if we think about it taking in consideration the formal structure of literary narrative. After all, developing a research observing how quotidianity appears in literature allows us to find out and comprehend the complexity of the social relations in the historical process as to examine the literary text regarding its historical effectiveness as its aesthetic force.